Study on Ministries Responsible For Various Categories of Disasters: Enhancing Disaster Response through Improved Institutional Arrangements and Resource Management (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Institutional arrangements fordisaster response are the heart of disaster management systems. There is nodearth of personnel, both civilian and military, experienced Institutionalarrangements for disaster response are the heart of disaster managementsystems. There is no dearth of personnel, both civilian and military,experienced in handling situations arising out of natural disasters. However,there certainly is a pressing need for improvement and strengthening ofexisting institutional arrangements and systems in this regard to make theinitial response to a disaster more effective and professional. Most of theresources and expertise needed already exist with the Government.  in handling situations arising out of naturaldisasters. However, there certainly is a pressing need for improvement andstrengthening of existing institutional arrangements and systems in this regardto make the initial response to a disaster more effective and professional.Most of the resources and expertise needed already exist with the Government.